The Inflammatory Basis of Atherosclerosis: Current Understanding and Future Therapeutic Directions - Asezebhobor Eseosa; Aluyor Abraham (Darul Yasin Al Sys, 2026)
Although atherosclerosis has increasingly been recognized as a chronic inflammatory disease, comprehensive reviews that integrate the inflammatory mechanisms underlying atherosclerotic progression remain limited. This review aims to synthesize current knowledge on inflammation-driven pathways in atherosclerotic lesion development and evaluate the clinical relevance of targeting these pathways. A narrative review approach was employed through examination of experimental studies, pathological evidence, and clinical trials identified from PubMed, Scopus, Web of Science, and Google Scholar, with literature selected based on its relevance to inflammatory mechanisms in atherosclerosis. The findings indicate that endothelial inflammatory responses initiate lesion development by promoting immune cell infiltration into the vessel wall, while persistent immune activity accelerates plaque growth and disease progression. Clinical evidence further shows that targeted anti-inflammatory therapies, particularly IL-1β inhibition and colchicine, can significantly reduce cardiovascular events, although therapeutic responses vary across patient populations. These findings support the evolving paradigm of atherosclerosis as an immune-mediated disease and clarify the interplay between inflammation, lipid metabolism, and vascular pathology. The review concludes that inflammation represents a central and therapeutically relevant mechanism in atherosclerosis. Its contribution lies in advancing cardiovascular immunology literature while offering practical implications for clinicians and policymakers to prioritize inflammation assessment and consider anti-inflammatory strategies in high-risk populations. Future research should further examine context-specific inflammatory phenotypes, optimal intervention timing, plaque-specific biomarkers, and the integration of anti-inflammatory approaches with existing cardiovascular therapies.